2002
DOI: 10.1901/jeab.2002.78-291
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of a Generalized Categorization Repertoire: Effect of Training With Multiple Domains, Samples, and Comparisons

Abstract: The present experiment explored the effects of three variables on the spontaneous categorization of stimuli in perceptually distinct and novel domains. Each of six stimulus domains was created by morphing two images that were the domain endpoints. The endpoints of the domains were male and female faces, two abstract drawings, a car and a truck, two banded-elevation satellite land images, a tree and a cat, and two false-color satellite images. The stimulus variants at each end of a domain defined two potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 57 publications
0
44
0
1
Order By: Relevance
“…For two decades, behavior analysts have studied the potential of Naming with respect to how it may or may not facilitate certain emergent categorization (Arntzen, 2004;Clayton & Hayes, 1999;Dugdale & Lowe, 1990;Fields et al, 2003;Guess & Baer, 1973;Hayes, 1989;Hayes, Barnes-Holmes, & Roche, 2001;Horne et al, 2004Horne et al, , 2006Keller & Bucher, 1979;Lee, 1981;Lowe & Beasty, 1987;Miguel & Petursdottir, 2009;Miguel, Petursdottir, Carr, & Michael, 2008;Randell & Remington, 2006;Shusterman & Kastak, 1993;Sidman, 1986Sidman, , 1992Smeets & Striefel, 1976;Stone, Miguel, & Gould, 2006;Stromer & McKay, 1996;Wynn & Smith, 2003;Zentall, Galizio, & Critchfield, 2002). See Miguel and Petursdottir for a comprehensive review of that literature.…”
Section: Naming As An Independent Variablementioning
confidence: 99%
See 1 more Smart Citation
“…For two decades, behavior analysts have studied the potential of Naming with respect to how it may or may not facilitate certain emergent categorization (Arntzen, 2004;Clayton & Hayes, 1999;Dugdale & Lowe, 1990;Fields et al, 2003;Guess & Baer, 1973;Hayes, 1989;Hayes, Barnes-Holmes, & Roche, 2001;Horne et al, 2004Horne et al, , 2006Keller & Bucher, 1979;Lee, 1981;Lowe & Beasty, 1987;Miguel & Petursdottir, 2009;Miguel, Petursdottir, Carr, & Michael, 2008;Randell & Remington, 2006;Shusterman & Kastak, 1993;Sidman, 1986Sidman, , 1992Smeets & Striefel, 1976;Stone, Miguel, & Gould, 2006;Stromer & McKay, 1996;Wynn & Smith, 2003;Zentall, Galizio, & Critchfield, 2002). See Miguel and Petursdottir for a comprehensive review of that literature.…”
Section: Naming As An Independent Variablementioning
confidence: 99%
“…The term multiple-exemplar instruction (or multiple-exemplar training) is used in several different ways and has a long history (Engelmann & Carnine, 1991;Fields et al, 2003;Greer & Lundquist, 1973). We point out these distinctions to clarify how we use this term.…”
Section: Identified Sources Of Namingmentioning
confidence: 99%
“…Becker (1992) presented extensive evidence that novel textual response emerged as a function of MEI from subsets of phonemic stimulus control. Others found that MEI produced complex auditory abstractions in humans and pigeons (Greer & Lundquist, 1976;Porter & Neuringer, 1985), and novel categorization of visual stimuli in humans (Fields, et al, 2003). These latter MEI procedures dealt with MEI for stimuli rather than MEI across responses to stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The term multiple exemplar instruction was used extensively in early research on "concepts" and abstraction (Becker, 1992;Fields et al, 2003;Greer & Lundquist, 1976) and has been used in the research on emergent verbal behavior (Fiorile & Greer, 2007;, 2007Greer, Yuan et al, 2005;NuzzoloGomez & Greer, 2004). The term multiple exemplar training is also used in a significant body of research (Barnes-Holmes, et al, 2001a, 2001bLuciano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation